2014
DOI: 10.11606/issn.2357-8041.v20i1p4-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sodium Ascorbate and Ascorbic Acid Hydrogels on Microleakage of Composite Restorations after an Office Bleaching Protocol

Abstract: Aim: This study evaluated the infl uence of 20% sodium ascorbate (SA) and 10% ascorbic acid (AA) hydrogels on the microleakage of class V composite restorations after an offi ce bleaching protocol (B). Methods: Sixty bovine incisors were sectioned at one point extending 8 mm from the amelodentinal junction toward the incisal edge, and at a second point extending 2 mm from the amelodentinal junction toward the root apex. Root canals were sealed with a composite and the teeth were divided into 5 groups. In Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…In order to meet the high aesthetic demands of the patients nowadays, replacing these restorations immediately after teeth bleaching is eventually mandatory, as described in this case report. With regards to these situations where the dentist cannot wait the seven days intended for the optimal replacement of the restorations [8,9], many alternatives have been described in the literature [10][11][12] and the use of antioxidants is a handy one [9,11,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to meet the high aesthetic demands of the patients nowadays, replacing these restorations immediately after teeth bleaching is eventually mandatory, as described in this case report. With regards to these situations where the dentist cannot wait the seven days intended for the optimal replacement of the restorations [8,9], many alternatives have been described in the literature [10][11][12] and the use of antioxidants is a handy one [9,11,13,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the use of antioxidants can be highlighted since it seems to be a more effective alternative to reduce or remove the residual oxygen [11,14]. The sodium ascorbate is the most investigated antioxidant [9,[13][14][15] and despite its efficiency in reducing microleakage has been pointed out previously [15], there is still some controversy about its mechanisms [11]. Recent study [16] have shown promising results with the application of the 10% sodium bicarbonate (SB), present in whitening kits, for 5 min on bleached enamel.…”
Section: Introductionmentioning
confidence: 99%
“…5 To handle compromised bond strength of pre-bleached dental hard tissue, use antioxidant like sodium ascorbate. 2 , 5 , 7 , 8 , 9 , 14 , 15 As a practical approach, place 10% sodium ascorbate on the bleached surface for 10 minutes with agitation and rinse it with water before bonding. 2 …”
Section: Amentioning
confidence: 99%